2016
DOI: 10.1038/srep31857
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet disrupts metabolism in two generations of rats in a parent-of-origin specific manner

Abstract: Experimental and epidemiological evidence demonstrate that ancestral diet might contribute towards offspring health. This suggests that nutrition may be able to modify genetic or epigenetic information carried by germ cells (GCs). To examine if a parental high fat diet (HFD) influences metabolic health in two generations of offspring, GC-eGFP Sprague Dawley rats were weaned onto HFD (45% fat) or Control Diet (CD; 10% fat). At 19 weeks, founders (F0) were bred with controls, establishing the F1 generation. HFD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
36
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 48 publications
(70 reference statements)
9
36
2
Order By: Relevance
“…One previous study of ICR mice found that maternal WD decreased circulating adiponectin concentrations in adult offspring [15], but we did not observe such an effect. Circulating adiponectin concentration is expected to be strongly negatively related to body fat [e.g., 61,62], which, as noted in the previous paragraph, was not affected by maternal WD after 6 days of adult wheel access.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…One previous study of ICR mice found that maternal WD decreased circulating adiponectin concentrations in adult offspring [15], but we did not observe such an effect. Circulating adiponectin concentration is expected to be strongly negatively related to body fat [e.g., 61,62], which, as noted in the previous paragraph, was not affected by maternal WD after 6 days of adult wheel access.…”
Section: Discussioncontrasting
confidence: 99%
“…Offspring of dams receiving a high-fat diet may have higher corticosterone levels as adults [14]. Maternal high-fat diets may also lead to increased adult leptin [9,15,16] and decreased adiponectin [15]. Maternal overnutrition during this stage has also been reported to alter neurobiological processes, including dietary preferences, reward signaling, learning, and memory [e.g., 1720].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, nutritional status (both over- and undernutrition), insulin resistance, exercise, chemical exposure, and behavior in the parent before and during pregnancy can all affect both paternal and offspring health (Anderson et al, 2006; Anway et al, 2006; Chambers et al, 2016; Hanafi et al, 2016; Isganaitis et al, 2014; Jimenez-Chillaron et al, 2009; Murashov et al, 2016; Rodgers et al, 2013; Rodgers et al, 2015; Skinner et al, 2010; Stanford et al, 2015). …”
Section: Experimental Models Of Multigenerational Disease Riskmentioning
confidence: 99%
“… * Paternal contribution to expression of placental development genes a Ferguson-Smith et al, 2006; b Schagdarsurengin and Steger, 2016; c Saben et al, 2016; d Wu et al, 2015; e Wang et al, 2016; f Branco et al, 2016; g Huypens et al, 2016; h Chen et al, 2016; i Daxinger et al, 2016; j de Castro Barbosa et al, 2016; k Denham et al, 2015; l Donkin et al, 2016; m Hammoud et al, 2009; n Huypens et al, 2016; o Jodar et al, 2013; p Lane et al, 2014a; q McPherson et al, 2015; r Okada et al, 2010; s Ost et al, 2014; t Palmer et al, 2012; u Peng et al, 2012b; v Radford et al, 2014; w Rodgers et al, 2015; x Schuster et al, 2016; y Sharma et al, 2016; z Shea et al, 2015; aa Siklenka et al, 2015; ab Terashima et al, 2015; ac van de Werken et al, 2014; ad Seckl and Meaney, 2004; ae Alfaradhi and Ozanne, 2011; af Benz and Amann, 2010; ag Carone et al, 2010; ah Chambers et al, 2016; ai, aj Dunn and Bale, 2009, 20...…”
Section: Figurementioning
confidence: 99%
“…Most of the current evidence for the transgenerational influence of pregnancy‐related exposures has been derived using rodent models . For example, Chambers et al reported that offspring and grand‐offspring of rats fed a high‐fat diet (with the intermediate generation fed only a chow diet) had increased body weight compared to controls with the effect less pronounced in the grand‐offspring …”
Section: Introductionmentioning
confidence: 99%